ANALISIS DAYA SAING EKSPOR KOPI SUMATERA SELATAN DI PASAR ASEAN - Trilita Apriani (Journal of Business Administration (JBA), 2021)
Plantation is one of the most important and strategic sub-sectors in the socio-economic life of the people in South Sumatra Province. South Sumatra has a high amount of coffee production compared to other provinces, but in reality the average number of exports is not still relatively small compared to the results of its production. Descriptive research with a qualitative method was conducted intensively, in which researchers participated in the field, and conducted a comprehensive analysis of various documents found in the field. Primary data were obtained through interviews and observations, while secondary data were obtained from books, journals, reports, from various relevant agencies and from credible websites. Then, coffee export competitiveness is analyzed with Diamond Porter's Theory guidelines and strategy analysis with Porter's Generic Strategy. This study found that South Sumatra has competitive advantages including conditions with supporting natural resources so that the amount of production is abundant, but needs to be supported by factor conditions, more adequate infrastructure, such as access to plantation roads and seaports as access to export trade, and Improving the formulation of clear trade management policies. The strategy used to increase the competitiveness of South Sumatra coffee exports, namely by creating superior products in terms of differentiation, namely creating quality and different coffee, was built by creating a team of quality and integrity workers so as to create quality production from upstream to downstream, and offers competitive prices, so as to increase the competitiveness of South Sumatra coffee exports.